ANTESEDEN DAN KONSEKUENSI PEMASARAN HUBUNGAN DALAM INDUSTRI RITEL - Govi Arya Katita; Waluyo Budi Atmoko; Ariefah Yulandari (Conference on Innovation in Health, Accounting and Management Sciences (CIHAMS), 2020)
This study aims to examine the influence of antecedents and the consequences of relationship marketing in the retail industr y. Relationship marketing is depicted by the variable commitment, trust and satisfaction of the relationship felt by industr y customers. Antecedents in relationship marketing are mentioned because there is communication between customers and employees in the retail industr y. While the antecedent of relationship marketing is contagious communication which, if positive things are spread, will benefit the r etail industr y. Data obtained through questionnaires distributed to people who have already or are shopping at Lotte Grosir Surakarta. The research sample used amounted to 200. The sampling technique used was pur posive sampling by clustering two stages with consideration of districts in Surakarta. Hypothesis testing is done by using SEM (Structural Equation Modeling)analysis. The results in this study indicate that five hypotheses are supported and there is one hypothesis that is not supported. Relationship marketing in the form of commitment, trust, and relationship satisfaction that is felt by customers has a positive effect on communication. The better the relationship marketing is felt by the customer, the more often and the higher the likelihood that the customer is communicating is getting infected. Communication in this study has a positive influence on commitment and trust felt by customers. However, communication does not influence the satisfaction of the relationship by the customer.